Simple markers for subclinical inflammation in the different phases of bipolar affective disorder - YILDIZ, MESUT (UNIV SAO PAULO, INST PSIQUIATRIA, 2016)
Background: Recently, a growing number of publications have suggested that the immune-inflammatory system may be involved in the etiology of bipolar disorder (BD). Objective: The aim of this study was to investigate neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and red cell distribution width (RDW) in the three different phases of BD patients compared to each other and controls. Methods: One hundred eighty-seven bipolar patients (78 euthymic, 53 manic/hypomanic and 56 depressed), and 62 age and sex matched controls were enrolled. Sociodemographic variables and complete blood count parameters of the patients and the control group were recorded. Results: The groups did not differ from each other on the hematological parameters, except for NLR and RDW. Post-hoc analyses revealed that NLR values were significantly higher in the euthymic and manic/hypomanic bipolar groups compared to control group. In addition, post-hoc analyses revealed that RDW values were significantly higher in the manic/hypomanic bipolar group relative to the control group. Discussion: Longitudinal studies evaluating the levels of inflammatory markers in the early phases of the disorder, and their relationship with the development of different episodes and medical comorbidities may be useful to understand the role of inflammation in BD.
Keywords: Bipolar affective disorder; inflammation; neutrophil-lymphocyte ratio; platelet-lymphocyte ratio; red cell distribution width; TO-LYMPHOCYTE RATIO; NEUTROPHIL/LYMPHOCYTE RATIO; NEUTROPHIL-LYMPHOCYTE; PROGNOSTIC-FACTOR; PLATELET; DISEASE; COMORBIDITY; SCHIZOPHRENIA; PREVALENCE; REMISSION